Total Flavonoids Content in the Raw Material and Aqueous Extractives from Bauhinia monandra Kurz (Caesalpiniaceae). (4th June 2012) - Fernandes, Ana Josane Dantas; Ferreira, Magda Rhayanny Assunção; Randau, Karina Perrelli; de Souza, Tatiane Pereira; Soares, Luiz Alberto Lira
Abstract : The aim of this work was to evaluate the spectrophotometric methodology for determining the total flavonoid content (TFC) in herbal drug and derived products from Bauhinia monandra Kurz. Several analytical parameters from this method grounded on the complex formed between flavonoids and AlCl3 were evaluated such as herbal amount (0.25 to 1.25 g); solvent composition (ethanol 40 to 80%, v/v); as well as the reaction time and AlCl3 concentration (2 to 9%, w/v). The method was adjusted to aqueous extractives and its performance studied through precision, linearity and preliminary robustness. The results showed an important dependence of the method response from reaction time, AlCl3 concentration, sample amount, and solvent mixture. After choosing the optimized condition, the method was applied for the matrixes (herbal material and extractives), showing precision lower than 5% (for both parameters repeatability and intermediate precision), coefficient of determination higher than 0.99, and no important influence could be observed for slight variations from wavelength or AlCl3 concentration. Thus, it could be concluded that the evaluated analytical procedure was suitable to quantify the total flavonoid content in raw material and aqueous extractives from leaves of B. monandra .